Evaluation of alcohol and psychoactive substances in blood samples of drivers involved in traffic accidents - GÜLHAN, REZZAN (My University, 2011)
Objectives: Traffic accidents resulting from driving under the influence of drugs (DUID) are a serious problem throughout the world. This study evaluated the type of the psychoactive substances (with or without alcohol) detected in blood samples of drivers involved in traffic accidents in Istanbul and surrounding area. Materials and methods: The samples from individuals involved in traffic accidents were sent for analysis to the Council of Forensic Medicine-Istanbul Chemistry Department by police or judicial authorities between July 2010 and June 2011. Alcohol analysis was carried out by headspace HS/GC Perkin Elmer Clarus 500 GC TMHS 40. Psychoactive substances were detected using an immunoassay screening (Microgenics’ CEDIA Assay kits including Amphetamine/Ecstasy, Benzodiazepines, Barbiturates, Multilevel THC, Cocaine, Methadone, Opiate, TCA Antidepressants on Hitachi 911) followed by LC/MS/MS. Blood samples were subjected to solid phase extraction using Oaisis HLB(60 mg) cartridges. Cartridges were conditioned with 1 ml methanol and water respectively. Then 1.5ml blood was passed. Cartridge rinsed by 5% Methanol in water (v:v) and dried. And finally eluted 0.5 ml methanol, 0.5 ml 2% ammonia in methanol (v:v) and 0.5 ml 2% Acetic Acid in methanol(v:v) respectively. Analyses were performed on a Shimadzu LC-20A series system interfaced to a tandem mass spectrometry API 4000 with an electrospray Turbo V™ ion source in negative and positive mode. For positive mode the ESI source settings were ion spray voltage 5500 V, source temperature 500 °C, nebulation and heating gas (N2), 50 and 50 respectively. For negative mode the ESI source settings were ion spray voltage -4500 V, source temperature 500 °C, nebulation and heating gas (N2), 50 and 50 respectively. For chromatographic separation polar full endcapped phenylpropyl column was used at 40 °C. A mobile phase of water containing 0.2% formic acid and 2 mM Ammonium Formate (Solvent A) and acetonitrile containing 0.2% formic acid and 2 mM Ammonium Formate (Solvent B) was delivered with the following gradient: starting 10% B at 1ml/min, reaching 90% B in 10 min at 1ml/min, for 5 min 90% B at 1ml/min, back to 10% B in 2.5 min at 0.5 ml/min. Detection of the ions was performed in multiple reaction monitoring (MRM) mode. Analysis of the collected data was carried out by means of Analyst software (Applied Biosystems/Sciex). Results: Alcohol analysis was requested in 4274 traffic accident cases by legal authorities during this 1 yr period. However, the analysis of psychoactive substances along with alcohol was requested for only 92 cases. Blood analysis in 32 (35.1%) of these 92 suspected cases showed only alcohol; however, in 14 (15.2%) of cases at least one psychoactive substance was identified. There was neither alcohol nor psychoactive substances detected in 45 (49.4%) cases. Out of these 14 cases, in 8 (57.1%) both alcohol and psychoactive substances were identified and in 6 (42.8%) cases there was at least one psychoactive substance without alcohol. THC was the most frequent substance detected (n=8; 57.1%). Benzodiazepines ((n=4; midazolam (n=3) and diazepam (n=1)), pentobarbital (n=2), MDMA (n=1), and cocaine (n=1) were the other identified psychoactive substances in these blood samples. Conclusions: Analysis for both psychoactive substances and alcohol was requested in only 1.7% of traffic accident cases during the 1 yr investigation period, and fifteen percent of them contained at least one psychoactive substance with or without alcohol. These results indicate that although there are regulations, DUID is not well recognized and not inspected by police and legal authorities who are responsible in routine controls in Istanbul, Turkey. Psychoactive substances should be checked in all traffic accident cases along with alcohol.
Keywords: DUID; Drugged Driving; Alcohol